Penataan Hunian Kumuh Perkotaan di Atas Tanah Ulayat: Studi Kasus pada Kota Payakumbuh, Sumatera Barat - Noegroho, Noegi (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Slum areas are likely found in many cities in Indonesia although the government through the Ministry of Public Housing have rolled several programs to alleviate its existence. One example of slum areas is found in Payakumbuh, West Sumatra, where its land are mostly owned by local traditional folks knowned as ‘ulayat land’. A huge amount of poor houses are built on rented ulayat land. Regarding to the rent status, the housing arrangement on the area faces difficulties. Therefore, this article would like to give an overview of problems in the slums arrangement in Payakumbuh as well as giving some concepts for dealing with the problems associated with such land status owned by adat.